Photography annual 2007 - Pedersen, B. Martin, 1936- (Graphis, 2006)
Graphis Photography Annual 2007 is a moving collection of the year's best photographs. Shot by some of the world's most respocted photographers and selected from an international pool of entries, these beautifully reproduced images are organized by category for easy referencing. ThisYear's book includes interviews with Albert Watson on his lates work, "Shot in Vegas," Joel Meyerowitz on Aftarmath, a photographic documentation of the September 11th recovery effots, and Paolo Ventura on his recently relased collection, War Souvenir.
Obsahuje adresář
Keywords: fotografie; ročenky